Biographical sketch of Theodore Burr - Burr, Theodore
Biographical material concerning Burr's career as a bridge architect and builder.
Typewritten transcript.
Architect and builder of covered bridges in Pennsylvania. Born 1771; died 1822.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Architecture -- Pennsylvania; Bridges -- Pennsylvania; Architects